2020
DOI: 10.1002/pen.25615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of devulcanized rubber on the thermomechanical properties of expanded ethylene‐propylene diene monomers composites

Abstract: Various amounts of both devulcanized (DR) and non‐devulcanized (NDR) recycled rubber were melt compounded with a virgin ethylene‐propylene diene monomer (EPDM) rubber. The resulting compounds were then expanded by using azodicarbonamide. The role played by the presence of DR or NDR on the thermomechanical properties of the obtained materials was evaluated. Electron scanning microscope micrographs highlighted that DR particles were better encapsulated within the EPDM matrix with respect to the corresponding NDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Moreover, the mechanical properties of microcellular SR/EPDM foams in this paper are higher than those of EPDM foams reported in existing literature. [ 2,40–42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the mechanical properties of microcellular SR/EPDM foams in this paper are higher than those of EPDM foams reported in existing literature. [ 2,40–42 ]…”
Section: Resultsmentioning
confidence: 99%
“…In conventional suspension polymerization, the low compatibility of graphite with styrene monomer and its own agglomeration tendency prevent the homogeneous dispersion of graphite in the organic phase, resulting in instability of the polymerization process. [33][34][35][36][37] In suspension polymerization, the monomer and graphite are suspended as small droplets in the dispersion medium for polymerization. In small droplets, styrene monomer (0.909 g/cm 3 ) and graphite (2.09-2.33 g/cm 3 ) are subjected to different gravitational and centrifugal forces of rotation and revolution due to their different densities.…”
Section: The Effect Of Homogeneous Dissolution On the Reaction Systemmentioning
confidence: 99%
“…[8] In this regard, the effect of GTR on the functional properties of some foamed polymers such as low-density polyethylene (LDPE), [9,10] polypropylene (PP), [11][12][13][14][15][16] polyurethane (PU), [17][18][19] among others has been reported. [20,21] Those studies indicated that the incorporation of elastomeric filler as GTR powder into polyolefin enhanced the structural and mechanical properties of the foamed compounds.…”
Section: Introductionmentioning
confidence: 99%